Kalimāt-i qiṣār-i Imām ʿAlī : Du majmūʿa: 1. Miʾat kalima - Nathr al-laʾālī, 2. Tarjuma-yi manẓūm-i Nathr al-laʾālī - Tabrīzī, Yār ʿAlī ʿAlānawī, (Miras Maktoob, ISBN: 9789004365452., 2019)
Being the first imam of the Shīʿa, ʿAlī b. Abī Ṭālib's (d. 40/661) statements-in any form-have always been important. In the centuries following his death, there appeared several collections of aphorisms, speeches, sermons, rulings and letters, all ascribed to him. The significance of these works was not just informative or even literary; they also had a didactic side insofar as ʿAlī was regarded as a channel for God's grace to man, it being through him that man could learn how to fulfil God's wish of obeying Him. Among these works, there are the Miʾat kalima by Baḥr b. ʿAmr al-Jāḥiẓ (d. 255/868-69) and the Nathr al-laʾāliʾ , probably by Faḍl b. Ḥasan Ṭabarsī (d. 548/1153). The present volume contains the facsimile editions of a well-executed 19th-century copy of both of these Arabic texts, followed by a Persian translation into poetry of part of the Nathr al-laʾāliʾ by Yār ʿAlī ʿAlānawī Tabrīzī (early 16th century)